Pengaruh Herding Bias dan Overconfidence Bias terhadap Pengambilan Keputusan Investasi - Ni Kadek Sinarwati; I Wayan Rona (Universitas Prasetiya Mulya, 2021)
This research study was conducted to analyze the effect of herding bias and overconfidence bias on investment decision-making. This research used quantitative methods with data collection techniques using questionnaires distributed to individual investors who have experience with a total sample of about 124 respondents. The technique used for sampling in this research was simple random sampling. The research analysis methods used the classical assumption test such as normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression analysis, namely hypothesis testing. According to the analysis, the result of this research is that herding bias and confidence bias had a positive and significant effect on investment decision-making.